1996
DOI: 10.1097/00006123-199609000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Functional Magnetic Resonance Imaging Mapping of the Motor Cortex in Patients with Cerebral Tumors

Abstract: FMRI of tactile, motor, and language tasks is feasible in patients with cerebral tumors. FMRI shows promise as a means of determining the risk of a postoperative motor deficit from surgical resection of frontal or parietal tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 23 publications
3
68
0
2
Order By: Relevance
“…Activated cortical regions typically coincide with the expected anatomical domains specific for the function tested. Not only do these domains agree with expected anatomical correlates, but confirmation through electrophysiologic testing has been performed with excellent concordance [1, 3, 4, 5, 6, 7, 8]. …”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Activated cortical regions typically coincide with the expected anatomical domains specific for the function tested. Not only do these domains agree with expected anatomical correlates, but confirmation through electrophysiologic testing has been performed with excellent concordance [1, 3, 4, 5, 6, 7, 8]. …”
Section: Discussionmentioning
confidence: 84%
“…Third, immature developmental status, especially in the infant population, restricts elaborate language-mapping paradigms currently being used in older children and adults. The preoperative use of fMRI in children has been briefly addressed in previous works [2, 8, 9, 23, 24]. All of these investigators recognized age limitations with functional imaging in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is clearly supported by several reliability studies, where considerable differences between the results of repeated measurements are reported [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Many factors such as magnetic field inhomogeneities, involuntary movements, respiration, cyclic heart function, and so on do have substantial influence on fMRI results [19][20][21][22][23][24][25][26]. Besides these well understood factors, there are less apparent parameters including the subject's attention [10,[27][28][29][30][31] and the subject's emotional state which are discussed to influence fMRI results as well.…”
Section: Introductionmentioning
confidence: 69%
“…Assessing the prognostic value of preoperative fMRI studies, Mueller et al observed that in patients with > 2 cm between the margin of the tumor and activated areas, no decline in motor function occurred as a result of tumor resection [10]. Furthermore, the technique has been used to localize cortical motor areas of residual function in the vicinity of intracerebral gliomas in order to direct therapy away from these regions [9].…”
Section: Motor Studiesmentioning
confidence: 99%